Risk modeling, assessment, and management - Haimes, Yacov Y., 1936-2022 (Wiley, 2016)
"This book examines risk analysis, focusing on quantifying risk and constructing probability in conjunction with real-world decision-making problems, including institutional, organizational,and political considerations"--Resumé vydavatele
Keywords: riziková analýza; rizikový management; riziko; matematické modelování; rozhodování; risk analysis; risk management; risk; mathematical modeling; decision making; případové studie; monografie; case studies; monographs